THE RELATIONSHIP BETWEEN CHILDREARING PRACTICES TO THE EMOTIONAL INTELLIGENCE OF INDONESIAN STUDENTS OF ADVENTIST UNIVERSITY OF THE PHILIPPINES - Suneeta Joys Sihombing dan Ketty Mondoringin (Jurnal Psikologi Pendidikan dan Pengembangan SDM, 2019)
This study sought to determine the relationship between child rearing practices to the Emotional Intelligence of Adventist University of Philippines (AUP) Indonesian students. In this study the researcher would brought up several considered question such as the profile of the respondents, the categories of the emotional intelligence of AUP Indonesian students as a whole and also to understand the childrearing practice of AUP Indonesian students’ parent and to see how would it be related to the emotional intelligence of AUP Indonesian students. In adding up to the understanding of the relationship of childrearing practices and emotional intelligence of AUP Indonesian students taken as a whole, the researcher would also include the moderator variables which are gender and the socio-economic status as well as to breakdown the relationship of childrearing practices with each emotional intelligence subscales that consist of 15 subscales. Methodology used for the study is a correlation design. The population consisted of 45 Indonesian students of the AUP, with the average age of 18 – 22 years old. Twenty-two of them are females and twenty-three are males. The instruments are two separate test (Parenting style and BarOn Emotional Quotient Test). This study therefore concludes that the emotional Intelligence of AUP Indonesian student is influenced by the childrearing practices of their parents. Other factors that also correlated are gender and socio-economic status. The fifteen area of emotional intelligence are also influenced by the childrearing practices except, the emotional self-awareness, empathy, stress tolerance, and problem solving. Keywords: Childrearing Practices, Emotional Intelligence, Gender, Socio-economic Status